Framing the Muslim subject, contesting the secular citizen: Tablighi Jamaat and the (trans)nationalization of Islam in Singapore - Woods, Orlando (Global networks (Oxford), 2023)
This paper explores how the (trans)nationalization of Islam can lead to differential understandings of the Muslim subject and secular citizen in Singapore. (Trans)nationalization problematizes the state‐led regulation of religion by revealing the complexities that emerge when religious subject positions are indexed to citizenship status. Islamic expression is closely regulated in Singapore, meaning the Singaporean Muslim subject is framed by the state in secular‐first terms. Complicating this framing is the presence of Bangladeshi migrant workers, who, by virtue of their visa and residency statuses, are viewed as transient members of society and denied access to citizenship. Non‐citizenship causes a variety of Islamic expressions to become viable pathways to religious subject formation, including those associated with Islamic missionary movement, Tablighi Jamaat. By claiming these subject positions, Bangladeshi Tablighis become vectors through which Singapore's Muslim spaces are exposed to transnational Islamic influences, causing the mosque to be imbued with divergent, and sometimes contested, meanings and attributions of value.